Phenotypic and functional characterisation of monocytic microparticles (mMP) derived from U937 and THP-1 cell lines - Ariffin, Nur Azrah Fazera Mohd (2018)
Monocytic microparticles (mMP) are 0.1-1.0 μm membrane particle, shed from human monocytes under physiological condition such as cellular activation and apoptosis or during certain pathological conditions. It has been reported in the literatures that mMP play important roles in inflammation, endothelial cell function and blood coagulation, however, the mechanism involved is still unclear. Monocytic MP can be characterised by the expression of their parental cell antigen, CD14 along with phosphatidylserine (PS) on mMP surface which can be detected by flow cytometry. This study was conducted using U937 and THP-1 monocytic cell lines. To induce mMP production in vitro, 1 x 106 cells were stimulated with 1 μg/mL lipopolysaccharide (LPS) or 10 ng/mL recombinant human tumor necrosis factor-α (TNF-α) for 18 hours in 5% CO2 humidified incubator at 37°C. Then, mMP were isolated through three differential centrifugations: (i) 500 xg to remove cell pellet, (ii) 1,500 xg to remove cell debris and (iii) 20,000 xg ultra-centrifugation to pellet mMP. This study was aimed to identify mMP surface marker expression by flow cytometry, measure mMP-induced proinflammatory cytokine secretions and assess coagulation potential of mMP. Theoretically, mMP populations are defined as positive for Annexin-V in combination with monocytic marker, CD14. Our finding has shown that U937 mMP and THP-1 mMP does not necessarily follow the same surface antigen expression as their parent cells. We then investigated the ability of mMP to secrete proinflammatory cytokines; TNF-α and interleukin 1 beta (IL-1β) and also tested mMP potential to modulate cytokine secretions in U937 and THP-1 cells. We found that IL-1β was secreted from both mMP but was down regulated when co-cultured with U937 and THP-1 cells. TNF-α was secreted from all TNF-α-stimulated samples and only mMPderived U937 upregulated TNF-α secretion almost up to 400 pg/mL from TNF-α- stimulated U937 cells. Besides that, mMP may have a procoagulant potential as shown by high expression of CD142 on both mMP surface and shorter prothrombin time (PT) over an increasing number of mMP. In conclusion, different monocytic cells may give rise to different properties of mMP. Further study should be carried out to establish a detail characterisation of mMP isolated from human blood and discover the clinical implications of mMP especially in inflammation-related diseases.